1995
DOI: 10.1097/00012272-199509000-00005
|View full text |Cite
|
Sign up to set email alerts
|

"Methodological notes on empathy": Further considerations

Abstract: This article updates and extends Jeannette Gagan's "Methodological notes on empathy," published in the January 1983 issue of ANS. The evolving conceptualization of empathy as a complex, intrapsychic, and interpersonal process suggests that the inconclusiveness and apparent contradictions of research to date might be substantially clarified by considering data from a multidimensional perspective. Attention to the conceptual bases underlying diverse measurement approaches is key to understanding the data produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 29 publications
1
29
0
1
Order By: Relevance
“…This subtest was dropped in the revised version because of its nonsignificant predictive validity concerning therapeutic outcomes (Barrett-Lennard, 1986). Subsequent versions of the Relationship Inventory have been developed for use in nonclinical situations involving family, friendship, coworker, and teacher-pupil relationships (Bennett, 1995).…”
Section: Other Instrumentsmentioning
confidence: 99%
“…This subtest was dropped in the revised version because of its nonsignificant predictive validity concerning therapeutic outcomes (Barrett-Lennard, 1986). Subsequent versions of the Relationship Inventory have been developed for use in nonclinical situations involving family, friendship, coworker, and teacher-pupil relationships (Bennett, 1995).…”
Section: Other Instrumentsmentioning
confidence: 99%
“…This argument, however, does not convince all critics (Gelso & Carter 1985;Bergman, 1967). Bennett (1995) argued that many of the difficulties regarding the concept are due to lack of clarity from Rogers and his subsequent lack of detailed discussion of the problems raised. Thus echoing the concerns with respect to empathy.…”
Section: Empathymentioning
confidence: 99%
“…a lack of clinical distinction between the therapist's intraphysic process of empathy and his or her response of being empathic" (Book, 1988, p. 422). Similarly, Bennett (1995) describes empathy as a complex intrapsychic and interpersonal process. Barrett-Lennard (1981) pointed out that even in this early definition Rogers (1957) made distinctions between "feeling into" and "feeling-with."…”
mentioning
confidence: 99%
“…Also, as a result of conceptualizing empathy from a borrowed perspective, theoretical and methodological problems in nursing studies have persisted, and conflicting findings have been reported (Bennett, 1995;Gagan, 1983;Olsen, 1991). In fact, some researchers have even begun to question the conceptual fit of empathy for nursing (Diers, 1990;Gordon, 1983;Morse et al, 1992;Pike, 1990).…”
Section: Empathymentioning
confidence: 99%
“…For many years, the application of borrowed theories of empathy to the nurse-patient relationship has been questioned by nurse educators and researchers (Bennett, 1995). In fact, over 15 years ago, Gagan (1983) challenged the nursing community to examine the nature and characteristics of empathy within the confines of the nurse-client relationship.…”
mentioning
confidence: 99%